A South African perspective on the tax implications of virtual asset accumulation and transactions stemming from persistent virtual worlds - Haupt, Alexander (Rhodes University, Faculty of Commerce, Department of Accounting, 2012)
Massively multiplayer online role-playing games are growing in popularity with millions of people participating in these persistent online environments on a daily basis. Accompanying the ever-increasing subscription numbers is an increase in real money trade transactions stemming from these game worlds. The research question to be addressed in this thesis is whether transactions stemming from virtual worlds have real-world taxation consequences. The goal of this research is to determine the taxability of virtual assets obtained in structured as well as unstructured virtual environments and to attempt to establish the differences between capital and revenue receipts in these virtual realms, taking into account the nature of a receipt. The general deduction formula is applied to establish the deductibility of expenditure incurred whilst participating in these virtual environments. Sundry matters such as Value-Added Tax, donations tax, the withholding tax on gambling gains and tax avoidance will also be addressed. The methodology adopted for the research could best be described as interpretative, aimed at analysing and interpreting the relationship between real world taxes and persistent virtual worlds and the transactions that stem from participation therein. The research is based purely on documentary evidence. After applying relevant tax legislation to virtual economies it became evident that merely because virtual assets only exist in virtual reality does not necessarily preclude them real world tax consequences. It was concluded, however, that it is not practical for the South African Revenue Service to monitor all virtual world transactions or for participant taxpayers to calculate the real world value of each and every asset acquired in-world. As a result, it was concluded that real world tax consequences should only be applied in situations where participants actually convert their virtual assets into real world currency.
Keywords: Uncatalogued